Trademark and Unfair Competition Conflicts Historical-Comparative, Doctrinal, and Economic Perspectives - Dornis, Tim W. (Social Sciences, 2017)
This book will be of interest for all jurists doing research and working practically in intellectual property law and international economic law. It should be an element of the base stock for every law school library and specialized law firm. This title is available as Open Access.